Enhancing the Predictive Utility of MHR for Senile Osteoporosis: Unaddressed Considerations and Future Directions [Response to Letter] - Lin N; Li D; Lin S; Ke Y; Lu J; Wu Y; Huang T; Hong H (Clinical Interventions in Aging, 2024)
Dang Li,1,2 Nan Lin1 1Fujian Key Laboratory of Vascular Aging, Department of Geriatrics, Fujian Institute of Geriatrics, Fujian Clinical Research Center for Senile Vascular Aging and Brain Aging, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China; 2Nursing Department, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of ChinaCorrespondence: Nan Lin, Department of Geriatrics, Fujian Medical University Union Hospital, 29 Xinquan Road, Fuzhou, Fujian, 350001, People’s Republic of China, Email lenorelin@163.com